Towards elicitation of users requirements for hospital information system: from a care process modelling technique to a web based collaborative tool. - Staccini, Pascal M. (American Medical Informatics Association, 2002)
Growing attention is being given to the use of process modeling methodology for user requirements elicitation. In the analysis phase of hospital information systems, the usefulness of care-process models has been investigated to evaluate the conceptual applicability and practical understandability by clinical staff and members of users teams. Nevertheless, there still remains a gap between users and analysts in their mutual ability to share conceptual views and vocabulary, keeping the meaning of clinical context while providing elements for analysis. One of the solutions for filling this gap is to consider the process model itself in the role of a hub as a centralized means of facilitating communication between team members. Starting with a robust and descriptive technique for process modeling called IDEF0/SADT, we refined the basic data model by extracting concepts from ISO 9000 process analysis and from enterprise ontology. We defined a web-based architecture to serve as a collaborative tool and implemented it using an object-oriented database. The prospects of such a tool are discussed notably regarding to its ability to generate data dictionaries and to be used as a navigation tool through the medium of hospital-wide documentation.